Air pollution tolerance index of Mangifera indica plant species growing in the greater Dhaka region, Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2019)
Air pollution tolerance index (APTI) of the mango (Mangifera indica) leaves growing in the greater Dhaka region, Bangladesh was studied. Leaf samples were collected in winter season from both roadsides and residential locations of different parts of greater Dhaka region. The APTI values of the leaves were calculated from the total chlorophyll content (TCC), ascorbic acid concentration, relative water content (RWC), and pH of the leaf extract. Determined APTI values were compared with Particulate Matter (PM2.5) values in each sampling location. TCC and ascorbic acid concentration were determined with a UV-Visible spectrophotometer. TCC values varied between 0.25 and 1.10 mg/g with an average of 0.66 mg/g. The average concentration of ascorbic acid was 2.21 mg/g (values ranging from 0.33 to 3.24 mg/g) and the RWC varied from 81.5% to 97.4%. Moreover, pH values of the leaf extracts were found acidic (4.48-5.78). The average APTI values varied depending on the locations with a total average of 10.1. However, the average APTI value in the residential area (10.5) was slightly higher compared to roadsides (9.70) indicating the existence of high-level pollutions at the roadsides. The highest APTI value was observed in Dhaka city sampling location (10.6) where the lowest value was found in Narayangonj (9.70). APTI values showed a strong correlation with particulate matter concentrations (PM2.5). These results suggest that Mangifera indica is very sensitive to the air pollutants.J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(1): 1-12